2013
DOI: 10.13005/ojc/290240
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Niobium (V) and Tantalum(V) Chelates with 2-aminothiophenol and 2-aminophenol

Abstract: Niobium(V) and Tantalum(V) Complexes [MLX 4 ] (where M = Nb/Ta; X = Cl/NCS; L = 2-aminothiophenol or 2-aminophenol) have been synthesised and characterised on the basis of elemental analysis, conductivity measurements, Ir, UV-vis and 'H NMR studies. The ligands behaves as mononegative bidentate donor. The value of magnetic moment of 0.35 -0.43 BM is a consequence of combined effects of spin-orbit coupling and distortions of the ligand field from a full octahedral symmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…These microalgae produce numerous valuable compounds such as polyunsaturated fatty acids (PUFA) and pigment. Many studies have been reported its wide applications, ranging from agricultural, ecological, bioenergy to pharmacology (antibacterial, antifungal, anticancer, anti-inflammation) [2].…”
Section: Introductionmentioning
confidence: 99%
“…These microalgae produce numerous valuable compounds such as polyunsaturated fatty acids (PUFA) and pigment. Many studies have been reported its wide applications, ranging from agricultural, ecological, bioenergy to pharmacology (antibacterial, antifungal, anticancer, anti-inflammation) [2].…”
Section: Introductionmentioning
confidence: 99%